Clinical Spectrum, Management, and Outcome of Rectovaginal Fistulae - Silindokuhle Revivial Sibiya; Surandhra Ramphal; Thandinkosi Madiba; Frank Anderson (The Annals of African Surgery, 2022)
Background: There are limited reports on rectovaginal fistulae in South Africa. Methods: This was a prospective analysis of all patients undergoing treatment for RVF at a tertiary referral hospital. Data was extracted from the database between 2006 and 2018 and analysis included demographics, aetiology, management, and outcome. The main outcome measure was healing of the fistula. Results: Fifty patients were identified [Median age 36 (IQR 28-42) years]. HIV status was positive (31), negative (5) and unknown (14). Commonest causes were obstetric (17), perineal sepsis (14) and spontaneous (8) (Table 2). Median duration of symptoms was 34.5 months (IQR 5-72) (Diagram 1). Forty-two patients underwent 55 surgical procedures (including 14 redos). In 32 patients RVF repair was undertaken under colostomy cover and 28/42 fistulae healed after the initial repair (66.7%), final success rate was (41/42) 97.6%. Two of eight fistulae healed after non-operative management (25%). Conclusion: Obstetric injury was the leading cause of RVF. HIV positive patients predominated. Spontaneous fistulae were seen in immunocompromised patients. Success rate was 97.6% over a healing time of 3 months. Non-operative management led to healing in 25% of cases.